Sadness, Gender and Empathy: Amarna and Post-Amarna (18th Dynasty) Mourning Scenes from the Egyptian Memphite Necropolis - Vivas Sainz, Inmaculada (Eikón / Imago, 2021)
This paper is focused on private tomb scenes with mourners dated to the end of the 18th Dynasty located in the Egyptian Memphite necropolis, with a special interest on the artistic resources and the clear division of groups according to the gender of mourners, as mourning men in expressive attitudes are particularly rare in ancient Egyptian scenes. The presence of men in grief, together with the traditional female mourners, within the funerary procession is striking, portraying expressive poses which provoke feeling of empathy and sorrow in the beholder. Indeed, the expressions of feelings in mourning scenes and their diverse artistic treatment in Memphite tomb decoration reveals the innovation and originality of the artists, features that could be traced back to the reign of Akhenaten. This paper explores the complex process of creation of the funerary iconography of the Post-Amarna art, a period of religious, political and social changes which were mirrored in private tomb scenes.